Synthesis and biological evaluation of 18F-labelled dopamine D3 receptor selective ligands. (15th April 2022) - Ji, Linyang; Fang, Yi; Tang, Jie; Liu, Chunyi; Huang, Caiyun; Hu, Qianyue; Li, Qingming; Chen, Zhengping
Graphical abstract: Highlights: Three novel 18 F-labelled phenylpiperazine-like radioligands were synthesized as potential novel PET probes for D3 R imaging. A simple, rapid and efficient 18 F-labelling method was developed. Radioligand [ 18 F]8b could quickly penetrate the blood-brain barrier and showed high affinity and selectivity to the dopamine D3 receptor. Radioligand [ 18 F]8b showed its good in vivo stability with negligible defluorination. Abstract: The dopamine D3 receptor (D3 R) is highly expressed in the limbic regions of the brain and closely related to a variety of neurological disorders including Parkinson's disease, schizophrenia and drug-seeking behavior. In vivo imaging of D3 R with radio-labelled tracers and positron emission tomography (PET) has become a powerful technique in related disorders. In this study, we synthesized three novel aromatically 18 F-labelled phenylpiperazine-like D3 R selective radioactive ligands ([ 18 F]5b, [ 18 F]8b and [ 18 F]11b ) and developed a simple, rapid and efficient 18 F-labelling method by condition optimization. Radiosynthesis of [ 18 F]5b, [ 18 F]8b and [ 18 F]11b was achieved by 18 F-fluorination from nitroarene precursors. Final radiochemical purities of [ 18 F]5b, [ 18 F]8b and [ 18 F]11b solution were > 99% and remained good stability (> 98% for up to 6 h) in PBS and FBS. PET imaging and cellular binding studies revealed that [ 18 F]8b had a higher D3 R affinity than [ 18 F]5b and [ 18 F]11b . Autoradiography and biodistribution studies of the brain showed that [ 18 F]8b had medium intensity specific accumulation in the striatum and cortex. Meanwhile, the low skeletal uptake of [ 18 F]8b revealed a good in vivo stability with negligible defluorination. These results indicated that [ 18 F]8b might be a potential 18 F-labelled D3 R PET imaging agent.